Avaliação de Desempenho da Técnica de Offloading Computacional em Nuvens Móveis - Junior, Warley; Henrique, Adriano; Lopes, Kelvin (Proceedings of the Workshop on Performance of Computer and Communication Systems (WPerformance), 2015)
Despite the advances in hardware for mobile devices, it is well-known that they are still limited with regard to processing, storage and energy resources as compared to desktops and servers. The Mobile Cloud Computing (MCC) paradigm provides an opportunity to extend the computational and energy resources of mobile devices through the use of offloading techniques. However, the MCC offloading does not always benefits energy consumption, but may depend on the wireless access technology. This paper presents a performance evaluation of computational offloading technique in a mobile cloud environment. The study highlights the impact of MCC use via Wi-Fi networks (Wireless Fidelity) and 4G LTE (Long Term Evolution) on battery lifetime and the mobile device processor occupancy time by using computational offloading.